Why do English players fail in soccer penalty shootouts? A study of team status, self-regulation, and choking under pressure - Jordet, G. (Journal of Sports Sciences, 2009)
I examine why players from some nations appear always to choke in major international soccer penalty shootouts. Based on a model on choking under pressure as a type of self-defeating behaviour (Baumeister, 1997), I hypothesized that highly favourable public appraisals of a team would be linked to displays of escapist self-regulation strategies and inferior performance. I selected the eight most merited European nations, obtained videos from penalty shootouts in two major international tournaments (World Cup and European Championships), and analysed all 200 shots taken by players representing these teams. The results showed significant relationships between team status, self-regulation strategies, and performance. Players from countries that, at the time of the penalty shootout, either had many international club titles or featured many internationally decorated players, spent less time preparing their shots and were less successful from the penalty spot than players from countries with lower public status. England and Spain are used to illustrate these effects, as the data suggest that players from these two countries may have underperformed in previous international soccer tournaments because of high public status and misguided self-regulation strategies.